Respon imun krustase - Manoppo, Henky; Kolopita, Magdalena E.F (e-Journal BUDIDAYA PERAIRAN, 2014)
Crustacean does not have adaptive immune system and mostly depends on innate or nonspecific immune response. This system can recognize and destroy foreign materials including pathogen. The nonspecific immune responses of crustacean consist of cellular and humoral responses. In cellular response, hemocyte plays an important role in body defenses to pathogen including virus, bacteria, fungi, and parasites. In humoral response, recognition of pathogen is mediated by protein and enzyme such as β-1,3-glucan-binding protein (BGBP), lipopolysaccharide-binding protein (LPS-BP), peptidoglycan recognition protein, phenoloxydase enzime. Keywords: crustacean, nonspecific immune response, cellular responses, humoral response, protein, enzime